Analysis of the regulatory phosphorylation site in Acanthamoeba myosin IC by using site-directed mutagenesis - Wang, Zhen-Yuan (National Academy of Sciences, 1998)
The actin-activated ATPase activity of Acanthamoeba myosin IC is stimulated 15- to 20-fold by phosphorylation of Ser-329 in the heavy chain. In most myosins, either glutamate or aspartate occupies this position, which lies within a surface loop that forms part of the actomyosin interface. To investigate the apparent need for a negative charge at this site, we mutated Ser-329 to alanine, asparagine, aspartate, or glutamate and coexpressed the Flag-tagged wild-type or mutant heavy chain and light chain in baculovirus-infected insect cells. Recombinant wild-type myosin IC was indistinguishable from myosin IC purified from Acanthamoeba as determined by (i) the dependence of its actin-activated ATPase activity on heavy-chain phosphorylation, (ii) the unusual triphasic dependence of its ATPase activity on the concentration of F-actin, (iii) its K(m) for ATP, and (iv) its ability to translocate actin filaments. The Ala and Asn mutants had the same low actin-activated ATPase activity as unphosphorylated wild-type myosin IC. The Glu mutant, like the phosphorylated wild-type protein, was 16-fold more active than unphosphorylated wild type, and the Asp mutant was 8-fold more active. The wild-type and mutant proteins had the same K(m) for ATP. Unphosphorylated wild-type protein and the Ala and Asn mutants were unable to translocate actin filaments, whereas the Glu mutant translocated filaments at the same velocity, and the Asp mutant at 50% the velocity, as phosphorylated wild-type proteins. These results demonstrate that an acidic amino acid can supply the negative charge in the surface loop required for the actin-dependent activities of Acanthamoeba myosin IC in vitro and indicate that the length of the side chain that delivers this charge is important.